Family physician performance from the perspective of Gilani customers - A Afkar; A Pourrza; V Khodabakhshi njad; F Mehrabian (Tehran University of Medical Sciences, 2013)
Background: The family physician program is considered to be one of the most remarkable reforms in the health care system which will probably Increase accessibility to physicians especially in deprived areas. This study aims to assess the strengths and weaknesses of family physician program in Fouman and Shaft cities in 1390.Materials and Methods: This is a descriptive cross-sectional and applied study in which all of the health care team`s members including family physicians, midwives, health workers, experts, technicians and also 856 individuals of service recipients in these two cities were involved .Data collection method was questionnaire of which. Validity and reliability was verified.Results: The most important strengths of family physician program and referral system from perspectives of service providers included: easy access of people to medical services and decreased medical cost for the patients and the main weaknesses were low salary for physicians, reverse referral and inaccessibility to family physicians round the clock. The main strengths from perspectives of service recipients were easy access to physicians and the main weaknesses were inappropriate reception of hospitals and lack of services through the 24 hours of the day.Conclusion: In order to eliminate the weaknesses and improve the quality of services, training the health staff in different levels of referral system, more comprehensive supervision, periodic assessments and effective supervision on the performance of family physician process owners is suggested